ANALISIS PERALIHAN HAK ATAS TANAH DAN BANGUNAN YANG DILAKUKAN SETELAH PERCERAIAN (STUDI PUTUSAN NOMOR 30/PDT.G/2013/PN.MTR) - HERMAWATI HERMAWATI (PREMISE LAW JURNAL, 2017)
Legitimate marriage gives legal consequence on joint property. The provisions regulate joint property in the Marriage Law No. 1/1974. This thesis analyzes the transfer of Land and Building Rights after a divorce and the Ruling No. 30/Pdt.G/2013/2013/PN.MTR. The research problems are as follows: how about legal protection for a married couple on joint property sold by one of them after the divorce, how about the legal domicile on land building rights of joint property which does not exist in the Marriage Certificate, and how about the judge’s legal consideration in the Ruling No. 30/Pdt.G/2013/2013/PN.MTR on the transfer of land rights after a divorce. The research used juridical normative and descriptive analytic method. Primary data were obtained from Law No. 1/1974 on Marriage, the Civil Code, and PP. No. 24/1997 on Land Registration, secondary data were obtained from books, and tertiary data were obtained from dictionaries and legal dictionary Keywords: Transfer, Land and Building Rights, Divorce